Methyl‐Induced Polarization Destabilizes the Noncovalent Interactions of N‐Methylated Lysines. Issue 42 (17th June 2021) - Rahman, Sanim; Wineman‐Fisher, Vered; Nagy, Péter R.; Al‐Hamdani, Yasmine; Tkatchenko, Alexandre; Varma, Sameer
Abstract: Lysine methylation can modify noncovalent interactions by altering lysine's hydrophobicity as well as its electronic structure. Although the ramifications of the former are documented, the effects of the latter remain largely unknown. Understanding the electronic structure is important for determining how biological methylation modulates protein−protein binding, and the impact of artificial methylation experiments in which methylated lysines are used as spectroscopic probes and protein crystallization facilitators. The benchmarked first‐principles calculations undertaken here reveal that methyl‐induced polarization weakens the electrostatic attraction of amines with protein functional groups – salt bridges, hydrogen bonds and cation‐π interactions weaken by as much as 10.3, 7.9 and 3.5  kT, respectively. Multipole analysis shows that weakened electrostatics is due to the altered inductive effects, which overcome increased attraction from methyl‐enhanced polarizability and dispersion. Due to their fundamental nature, these effects are expected to be present in many cases. A survey of methylated lysines in protein structures reveals several cases in which methyl‐induced polarization is the primary driver of altered noncovalent interactions; in these cases, destabilizations are found to be in the 0.6–4.7  kT range. The clearest case of where methyl‐induced polarization plays a dominant role in regulating biological function is that of the PHD1‐PHD2 domain, which recognizes lysine‐methylated states on histones. These results broaden our understanding of how methylation modulates noncovalent interactions. Abstract : Methylation of ammonium weakens its electrostatic attraction with protein functional groups ‐ salt bridges, hydrogen bonds and cation‐π interactions weaken by as much as 10.3, 7.9 and 3.5  kT, respectively. The weakened electrostatics is due to altered inductive effects that overcome increased attraction from methyl‐enhanced polarizability and dispersion. Due to their fundamental nature, these effects are expected to be widely present.